Slow Dieback of Grapevine: Association of Phialophora parasitica with Slow Dieback of Grapevines - Ferreira, J.H.S.; van Wyk, P.S.; Venter, E. (South African Journal of Enology and Viticulture, 2017)
Phialophora parasitica was consistently isolated from vines showing symptoms of slow dieback and decline. Pathogenicity tests were conducted on in vitro plantlets, grafted plants in a glasshouse and on graft unions. The fungus caused discolouration of wood as well as extensive plugging of xylem tissue.  Plugging material seemed to be of gum as well as parenchyma origin.  Callusing of graft unions was negatively affected.